2011
DOI: 10.1371/journal.pone.0025849
|View full text |Cite
|
Sign up to set email alerts
|

LITAF Mediation of Increased TNF-α Secretion from Inflamed Colonic Lamina Propria Macrophages

Abstract: Dysregulation of TNF-α in lamina propria macrophages (LPM) is a feature of inflammatory bowel diseases (IBD). LPS-Induced-TNF-Alpha-Factor (LITAF) is a transcription factor that mediates TNF-α expression. To determine whether LITAF participates in the mediation of TNF-α expression in acutely inflamed colonic tissues, we first established the TNBS-induced colonic inflammation model in C57BL/6 mice. LPM were harvested from non-inflamed and inflamed colonic tissue and inflammatory parameters TNF-α and LITAF mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Other experiments have shown that in diet-induced obesity, changes in macrophage function were revealed only after bacterial challenge (21). Lamina propria macrophages that were isolated from inflamed tissue had heightened TNF-α secretion, even without stimulation, suggesting that their environment altered their function (22). Thus, our finding that a role for CLR was only clearly demonstrated after inflammatory responses is paralleled by similar findings in other systems.…”
Section: Discussionsupporting
confidence: 87%
“…Other experiments have shown that in diet-induced obesity, changes in macrophage function were revealed only after bacterial challenge (21). Lamina propria macrophages that were isolated from inflamed tissue had heightened TNF-α secretion, even without stimulation, suggesting that their environment altered their function (22). Thus, our finding that a role for CLR was only clearly demonstrated after inflammatory responses is paralleled by similar findings in other systems.…”
Section: Discussionsupporting
confidence: 87%
“…Since TNF-α is mainly induced by the NF-κB, however celastrol is known to inhibit the NF-κB signal pathway [38]. Bushell et al [39] have discovered that TNF-α can be induced by the LPS-induced-TNF-α-Factor (LITAF) in inflamed colonic lamina propria macrophages, which is independent from NF-κB. We speculate that the invariant level of TNF-α between the saline group and the celastrol group may be produced via the LITAF signaling after the NF-κB inhibition based on the observation that no significant difference was found on the number of macrophages between the saline and celastrol groups.…”
Section: Discussionmentioning
confidence: 99%
“…Initially characterized as an LPS-dependent major TNF-α inducer, it was later reported that LITAF activation induces production not only of TNF-α but also of other inflammatory cytokines such as IL-1β and IL-6 [16], that LITAF is an important factor mediating macrophage activation during acute and chronic inflammation [15,31], and that its degree of activation determines sensitivity and resistance to LPS [16]. …”
Section: Discussionmentioning
confidence: 99%